Integrated Analysis of a Competing Endogenous RNA Network Reveals a Prognostic lncRNA Signature in Bladder Cancer - Peng, Mou; Cheng, Xu; Xiong, Wei; Yi, Lu; Wang, Yinhuai (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) acts as competing endogenous (ceRNA) to regulate mRNA expression through sponging microRNA in tumorigenesis and progression. However, following the discovery of new RNA interaction, the differentially expressed RNAs and ceRNA regulatory network are required to update. Our study comprehensively analyzed the differentially expressed RNA and corresponding ceRNA network and thus constructed a potentially predictive tool for prognosis. “DESeq2” was used to perform differential expression analysis. 206 differentially expressed (DE) lncRNAs, 222 DE miRNAs, and 2463 DE mRNAs were found in this study. The lncRNA-mRNA interactions in the miRcode database and the miRNA-mRNA interactions in the starBase, miRcode and mirTarBase databases were searched and a competing endogenous RNA (ceRNA) network with 186 nodes and 836 interactions was subsequently constructed. Aberrant expression patterns of lncRNA NR2F1-AS1 and lncRNA AC010168.2 were evaluated in two datasets (GSE89006, GSE31684) and real-time polymerase chain reaction was also performed to validate the expression pattern. Furthermore, we found these two lncRNAs are independent prognostic biomarkers to generate a prognostic lncRNA signature by univariate and multivariate Cox analysis. According to the lncRNA signature, patients in the high-risk group were associated with a poor prognosis and validated by an external dataset. A novel genomic-clinicopathologic nomogram to improve prognosis prediction of bladder cancer was further plotted and calibrated. Our study deepens the understanding of the regulatory ceRNA network and provides an easy-to-do genomic-clinicopathological nomogram to predict the prognosis in patients with bladder cancer.